Monjas, esposas y madres católicas: una panorámica de la feminización de la religión en España a mediados del siglo XIX - Raúl Mínguez Blasco (Amnis)
The feminization of religion has been a process not enough studied in Spain. The perception of the Catholic Church as an institution deeply settled down in the Old Regime and unable to react to the changes produced through nineteenth century is one of the causes that explains this relative absence of studies. Therefore, this paper tries to be a proposal to start filling the above mentioned historiographical gap. First, we will concentrate on the analysis of the catholic discourse on three concrete variants: the properly ecclesiastic discourse, across the work of Claret; the neocatólicos publicists discourse, across the work of Roca y Cornet; and the carlism discourse in a concrete moment, the Sexenio Democrático, across La Margarita, a weekly newspaper. The hypothesis we will agree is that the feminization of the catholic discourse in the middle of nineteenth century made possible the development of a form of religious life previously refused by the ecclesiastic hierarchy, the feminine congregations of active life. They tried to relieve what the Church considered to be negative effects of a society in an industrialization and secularization process.